The weather of the Pacific Northwest - Mass, Cliff (University of Washington Press, 2021)
""Fridays at ten of four is when we listen to our favorite person ever, Cliff Mass. If you don't know who Cliff Mass is, well, he's this thing me and Mom have, this awesome weather geek who loves weather so much you have no choice but to love him in return." - from Maria Semple's novel, Where'd You Go, Bernadette? This is a lavishly illustrated guide to making sense of the region's unique atmospheric and geographic forces. For the new edition of this contemporary classic, Cliff Mass has extensively revised and updated, as well as expanding his coverage of British Columbia as well as considering the impact of wildfires on the region's meteorology. A fascinating read, the book is indispensable to anyone who seeks a deeper understanding of the region's is weather"--